The Influence of Brand Image, Brand Trust, and Product Quality on Repurchase Intention for Aqua Bottled Drinking Water in DKI Jakarta - Amalia Nur Laili; Tine Yuliantini (International Humanities and Applied Science Journal, 2026)
This research aims to analyze the effects of Brand Image, Brand Trust, and Product Quality on Repurchase Intention of AQUA bottled drinking water products in DKI Jakarta. The subjects in this study were consumers who had purchased and consumed AQUA products in the DKI Jakarta area. The sample used in this study consisted of 280 respondents. This research employed a quantitative approach with a causal research design. The sampling technique used was non-probability sampling with purposive sampling method. Data were collected through the distribution of questionnaires using Google Form as the primary data source. The data analysis technique applied in this study was Structural Equation Modeling Partial Least Square (SEM-PLS) using SmartPLS 4.0. The results of this study indicate that (1) Brand Image has a positive and significant effect on Repurchase Intention, (2) Brand Trust has a positive and significant effect on Repurchase Intention, and (3) Product Quality has a positive and significant effect on Repurchase Intention. Keywords: Brand Image, Brand Trust, Product Quality, Repurchase Intention, AQUA